(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Globalisation has brought about drastic changes not just in terms of technology, but also in the field of education particularly for women who have been groping in the dark for ages without liberty, freedom, and individualism. Thanks to tremendous advances made in the field of science that great strides for women have opened novel pathways for tremendous literacy progress. Today, women are more revived up and connected to each other than ever before through literacy. The immense focus laid on the education of girls and women from the 21st century onwards has made motivating and passionate impact on girls and women to be educated highly. Eventually the literacy rate flared up in leaps and bounds and girls and women are now being educated with high qualifications and are making a mark in all fields. The article aims to throw light on literacy as a tool of empowerment for women.